Water Production from Atmospheric Air Using a Solar Water Recuperator by Glass Pyramid Device - Hussein Hayder Mohammed Ali; Suad H. Danook; Khadija O. Mohiuddin (Tikrit Journal of Engineering Sciences)
The present research examines the effect of the pyramid solar system's shape, notably the multi-bed pyramid, on the system's ability to gather water from the ambient atmosphere. In this research, a solar collector in the shape of a prism pyramid with 4 glass walls was designed and constructed. The collector stood at a height of (140 cm). The insulating layer at the pyramid's base was 15 cm thick, and its base was 100 cm × 100 cm. Thick panes of glass line the sides of the two pyramids (5 mm). The pyramid's interior included five levels of storage. Each shelf was about (20 cm) vertically apart. Each pyramidal unit's bed thickness is (10 cm). Saw wood and cloth were used as hosts in the collection process, and the calcium chloride (CaCl2) solution is used as a moisture absorber. Moisture was taken in from the atmosphere at night. During the day, solar energy evaporates the water that has been absorbed, and the water vapor condenses on the edges of the solar collector. The experimental findings demonstrated the potential to achieve an average water productivity of (1.25 L/day/m2) of surface area. The results also demonstrated that the pyramid coated with the CaCl2 solution-soaked cloth performed better than the other glass pyramid by roughly 5% on average daily in June 2022. It was deduced that this rise was caused by more CaCl2 solution being collected.